Assessing the Effectiveness of the Aceh Government’s Oversight of PT Bank Syariah Indonesia’s CSR Program - Riva Alzira; Helmi Helmi; Nofriadi Nofriadi; Mukhrijal Mukhrijal (Universitas Teuku Umar, 2026)
Corporate Social Responsibility (CSR) is a form of corporate social responsibility that contributes to supporting development and improving community welfare. The successful implementation of CSR programs is determined not only by the company's commitment but also by the effectiveness of government supervision as a regulator and facilitator. This study aims to analyze the effectiveness of the Aceh Government's supervision of the Corporate Social Responsibility (CSR) program of PT Bank Syariah Indonesia and to identify the challenges encountered in the implementation of such supervision. This study employed a qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using Budiani's effectiveness indicators, which include target accuracy, program socialization, program objectives, and program monitoring. The findings indicate that the Aceh Government's supervision of the CSR program of PT Bank Syariah Indonesia has been carried out through coordination, the provision of recommendations, and the verification of program beneficiaries. However, the effectiveness of the supervision has not been fully optimal due to the limited authority of the Aceh Government, the absence of operational regulations governing supervision mechanisms in detail, the low level of transparency in CSR program reporting, and the lack of an integrated monitoring and evaluation system. These conditions have resulted in supervision that remains primarily coordinative and has not been able to optimize the overall implementation of the CSR program. Nevertheless, the CSR program of PT Bank Syariah Indonesia has continued to contribute to the fields of education, healthcare, social welfare, and community economic empowerment.